アリルイソチオシアネート誘起急性胃粘膜炎症は実験動物の胃運動減弱を引き起こす ーサブスタンスPおよびカルシトニン遺伝子関連ペプチドの関与ー - 堀江, 俊治; 大重, 茉里奈; 藤井, 瑶子; 田嶋, 公人 (日本薬理学会年会要旨集, 2022)
We investigated the mechanism of acute inflammation induced by allyl isothiocyanate (AITC), a TRPA1 activator, through measurement of vascular permeability and gastric mucosal blood flow (GMBF) in rat stomachs to provide the rodent model of impaired gastric motility. Male SD rats were used after 18 h-fasting. Stomachs were mounted on the ex-vivo chambers in anesthetized rats. Vascular permeability (extravasated Evans blue) and GMBF (a leaser doppler) were measured in response to mucosal application of AITC. AITC obviously increased vascular permeability and GMBF. Gastric mucosal swelling was observed after application of AITC without hemorrhagic lesions. The both vascular permeability and GMBF in response to AITC were significantly attenuated by the pretreatment of a substance P receptor antagonist aprepitant, whereas GMBF was alone significantly decreased by the pretreatment of a TRPA1 blocker A-967079 and a calcitonin gene-related peptide (CGRP) receptor antagonist BIBN 4096. However, vascular permeability and GMBF in response to AITC hardly affected by the pretreatment of a mast cell stabilizer cromoglycate. These results suggest that AITC-induced acute inflammation with no mucosal damage is dependent on substance P and CGRP released from TRPA1-expressing nerves in rat stomachs, but not mast cells. Those inflammation could lead to the impaired motility in rodents.